2018
DOI: 10.1108/ijoa-08-2017-1213
|View full text |Cite
|
Sign up to set email alerts
|

Customer perceptions of CSR authenticity

Abstract: Purpose The purpose of this paper is to look at corporate social responsibility (CSR)-related actions to see whether they relate to clients’ perception of CSR. Design/methodology/approach Ninety-nine bank customers in Brisbane, Australia were surveyed by mail in a cross-sectional field study. Findings Not all CSR-related behaviors of the organizations were influential to perceptions of social responsibility. Big picture actions for the betterment of humanity were found to be influential to the perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 78 publications
4
16
0
Order By: Relevance
“…These results are aligned with the findings of Maignan (2001) and Venger and Pomirleanu (2018) confirming that customers have differences in prioritizing CSR aspects, and this is in accordance with their value orientations (Basil & Weber, 2006; Jose et al, 2018). As indicated by Siltaoja (2006), Golob et al (2008), and Rosario González‐Rodríguez et al (2019), individuals with self‐transcendence values expect companies to fulfill philanthropic activities more than individuals with self‐enhancement values.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…These results are aligned with the findings of Maignan (2001) and Venger and Pomirleanu (2018) confirming that customers have differences in prioritizing CSR aspects, and this is in accordance with their value orientations (Basil & Weber, 2006; Jose et al, 2018). As indicated by Siltaoja (2006), Golob et al (2008), and Rosario González‐Rodríguez et al (2019), individuals with self‐transcendence values expect companies to fulfill philanthropic activities more than individuals with self‐enhancement values.…”
Section: Methodssupporting
confidence: 88%
“…This means that respondents can clearly differentiate between economic, legal, ethical, and philanthropic aspects of CSR within the context of this study. The results showed customers with self-enhancement value orientation tend to have a higher purchase intention when they consider the economic aspect of CSR perfor- These results are aligned with the findings of Maignan (2001) and Venger and Pomirleanu (2018) confirming that customers have differences in prioritizing CSR aspects, and this is in accordance with their value orientations (Basil & Weber, 2006;Jose et al, 2018). As indicated by Siltaoja (2006), Golob et al (2008), and Rosario González- Unlike other stakeholder groups, bank customers' perception of ethical responsibility does not directly affect their purchase intentions.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…There are several studies conducted to assess the percepts of various stakeholder groups about various aspects of Islamic banking including the studies aimed at exploring the perceptions of customers including the studies by Gerrard and Cunningham, 1997;Metawa and Al-Mossawi,1998;Lee and Shakir, 2011;Echchabi and Olaniyi, 2012;Saeed et al, 2012;Fada and Webekwa, 2012;Ringim and Yussof, 2014;Ghani et al, 2015;Akhtar et al, 2016;Jose et al, 2018; studies analyzing the opinions of bankers including researches by Buchari et al, 2015;Shah et al 2016, Majeed and Zainab 2017, Riaz et al 2017, Aqib and Hussain, 2017Ali and Hassan, 2017;Ali et al, 2018;Majeed and Zainab, 2018; studies to evaluate the viewpoints of corporate customers including the research investigations by Ahmad and Haron, 2000;Rustam et al, 2011; and the analysis of perspectives of Shariah experts involved with IB industry in the study undertaken by Ayedh and Echchabi in 2015. The diverse studies undertaken in the past, on the assessment of stakeholders" perceptions included various aspects of Islamic banking. Some of these studies, in the context of this research, include the ones on Islamic banking ideals and objectives (Dusuki 2007, Dusuki 2008, Khan and Ramzan 2015; several other studies focused Islamic banking products/services quality and customer satisfaction (Khan et al, 2007;Abdullah and Kassim, 2009;Butt and Aftab, 2013;Ringim, 2014;Belwal and Maqbali, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been reported that skepticism can also arise from companies' deliberate use of CSR as a marketing strategy and as a means of charging higher prices for their goods (Bray, Johns, & Kilburn, 2011; Webb & Mohr, 1998). Such marketing schemes are detrimental to customer perception of firms (Jose, Khare, & Buchanan, 2018). The rise of consumer skepticism has also been attributed to organizations failure in walking their CSR talk (Lyon & Montgomery, 2015) or what is known as corporate hypocrisy (Connors, Anderson‐MacDonald, & Thomson, 2017; Fassin & Buelens, 2011).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%